Total syntheses of carbazole alkaloid mukoenine A and pyrano[3, 2-a]carbazole alkaloid girinimbine. (13th August 2022) - Nishiyama, Takashi; Kihara, Yuhto; Takeuchi, Nao; Mizuno, Shota; Hieda, Yuhzo; Hatae, Noriyuki; Choshi, Tominari
Abstract: In this study, we achieved the total synthesis of carbazole alkaloid mukoenine A through a seven-step sequence involving the construction of a carbazole framework using the electrocyclization of a 6π-electron system including an allene intermediate as the key step. Subsequently, the synthesis of pyrano[3, 2- a ]carbazole alkaloid girinimbine was achieved by the construction of the pyran ring via selenoetherification of the o-allylic phenol moiety of mukoenine A. Graphical abstract: Image 1 Highlights: The total synthesis of mukoenine A has been accomplished via a seven-step sequence. Girinimbine was synthesized by the construction of the pyran ring via mukoenine A. The carbazole framework was constructed by the allene-mediated electrocyclization.